SOB QUE MÁSCARA RETORNARÁ O RECALCADO? - Rosangela Aparecida Volpato (Universidade Estadual de Campinas, 2008)
Discussão acerca das idéias de Norbert Elias presentes no artigo "On Human Beings and their Emotions: a process-sociological essay", a fim de destacar as inovações em termos antropológicos e epistemológicos, nelas contidas. Palavras-Chave: Norbert Elias; Seres humanos; Emoções. Abstract A short discussion about Norbert Elias ideas included in his articles On Human Beings and their Emotions: a process-sociological essay, in order to highlight the innovations in anthropological terms and epistemological, in them contained. Key-Words: Norbert Elias; Human beings; Emotions.